Advanced Geogrid Reinforcement Strategies for Superior Bearing Capacity and Settlement Control in Square Shallow Foundations - Tawfeeq, Reem Siham; Salih, Bilal Muiassar M. (Salehan Institute of Higher Education, 2025)
Recently, many research studies on square-shaped soil foundations have failed to achieve acceptable results due to their low resistance, in addition to the expected settlement of these foundations when constructed on weak granular soil. This study aims to overcome the low resistance and excessive settlement of square shallow foundations on weak granular soils by developing advanced geogrid reinforcement strategies to enhance load-bearing capacity and control settlement. A series of scaled laboratory experiments were conducted on simulated weak soil profiles, varying three key parameters—the depth of geogrid reinforcement layers, the width of each geogrid layer, and the number of layers—while quantifying performance through the Bearing Capacity Ratio (BCR) and Settlement Reduction Ratio (SRR); these empirical results were complemented by theoretical derivations of novel mathematical models to predict reinforced foundation behavior under diverse difficulty conditions. Experimental outcomes reveal that multilayer geogrid systems substantially elevate BCR and diminish settlement, with optimal configurations achieving up to a 60% improvement in bearing capacity and a 50% reduction in settlement compared to unreinforced foundations, and that deeper placement and additional layers yield significant yet progressively smaller gains. The proposed approach uniquely employs insulating geogrid layers to prevent water ingress and moisture infiltration—preserving structural integrity and imparting anti-settlement properties—and introduces high-precision predictive models; furthermore, the multilayer arrangement creates a barrier against moisture migration, reducing long-term settlement risks under fluctuating groundwater conditions, and cost analysis indicates that the optimal configurations deliver superior performance with minimal additional material investment, offering a cost-effective and geotechnically sound solution for foundation engineering.